Réponses

2013-05-01T16:18:39+02:00

x/2 + 3 = 0

x/2        = -3

        x   = -3/1/2 =-3*2  =  - 6

 

 

 -x/5 +7  = -3

  -x/5       = -3 -7

  -x/5       =  -10

           x   = -10/-5

           x   =  2

 

x/10 +7 = -1

x/10      = -1-7

x/10      = -8

      x      = -8*10

      x       = - 80

 

-x/6-2 = 1

-x/6    =1+2

-x/6     =  3

   x      = 3* 6

   x       =  18

 

x-6 =3x

x-3x = 6

   -2x =6

     x = -6/2

     x  = -3

 

-3x+4 = 2x -1

-3x -2x = -1 -4

-5x     = - 5

    x     =  1

 

x/2 -5 = x+ 7

x/2 - x = 7 +5

 x/2 - 2x/2 = 12

- x/2   = 12

     x    =  12 * -2

     x    =  - 24

 

3(2-x) = 5x -7

6-3x   = 5x -7

-3x -5x  = -7 -6

-8x         =  -13

       x     = -13/ -8